A crystal violet based mechanochromic molecule, bulk polymer and applications thereof

CN121405608BActive Publication Date: 2026-10-30FUDAN UNIVERSITY
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202511631977.8
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2025-11-07
Publication Date
2026-10-30
Estimated Expiration
2045-11-07

AI Technical Summary

Technical Problem

[0007]本发明目的在于提供一种基于结晶紫内酰胺的力致变色分子、本体聚合物及其应用,以解决现有力致变色分子对机械力响应的专一性不足、结构修饰复杂、合成路线复杂等技术问题

Benefits of technology

本发明提供了一种基于结晶紫内酰胺的力致变色分子、本体聚合物及其应用,将力敏单元与可聚合功能基团的引入过程有机结合,有效简化了合成步骤,降低了制备成本,并为可控、专一的力致变色材料设计提供了新思路。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN121405608B_ABST
    Figure CN121405608B_ABST
Patent Text Reader

Abstract

The application discloses a crystal violet lactam-based force-induced color change molecule, a bulk polymer and application thereof, which organically combines a force sensing unit and a polymerizable functional group introduction process, effectively simplifies a synthesis step, reduces a preparation cost, and provides a new idea for controllable and specific force-induced color change material design. The application realizes accurate regulation of color and force-induced color change behavior through molecular structure optimization and polymer structure design. The molecule has the advantages of simple synthesis steps, cheap raw materials and low cost, can realize large-scale preparation, and exhibits stable and significant force-induced color change effect when a polymer material is mechanically compressed or stretched, so that the molecule has wide application prospects.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of mechanochromic technology, and in particular, to a mechanochromic molecule based on crystalline violet lactam, its bulk polymer, and its applications. Background Technology

[0002] Mechanophores are molecules that undergo specific chemical structural transformations under mechanical forces, thereby endowing polymer materials with the ability to sense and respond to mechanical stimuli, enabling the visualization and control of force-responsive functions. Common color-changing mechanophores include spiropyran, naphthopyran, oxazine, and rhodamine. These molecules typically generate colored species through mechanically induced chemical bond breaking or structural rearrangement, thus achieving the visual characterization of mechanical stress or deformation. These mechanophores have been widely used in research fields such as multicolor mechanically responsive materials, selective chemical bond activation, and precise control of reversible reactions.

[0003] However, most existing chromogenic force-sensitive molecules are not only sensitive to mechanical forces but also respond to light, heat, or chemical stimuli, thus weakening their mechanospecificity. Especially in practical applications, mechanical stress is often accompanied by changes in temperature or light, making it difficult to distinguish the source of the color response. Furthermore, force-sensitive molecules capable of achieving rapid, reversible force-induced color change based on covalent bond breaking are currently limited to oxazine systems; there is a lack of molecular systems that can regulate the force response from rapid to slow reversibility by altering the tension sites or polymer structure.

[0004] Meanwhile, the molecular design of mechanochromic molecules not only needs to consider the mechanochemical reaction pathway and reversibility, but also the simplicity and polymerizability of molecular synthesis. Most systems introduce functional groups that can be covalently linked to the polymer backbone, often leading to complex synthetic routes, increased costs, and difficulty in achieving large-scale, low-cost preparation.

[0005] Existing mechanochromic molecules (such as spiropyran and rhodamine) have technical problems such as susceptibility to light, heat or acid-base interference, difficulty in controlling mechanochromic behavior, insufficient performance stability, complex synthesis process, high cost, and unfavorable for large-scale application.

[0006] In general, most of the reported methanogenic molecules currently exist with the following problems: (1) They lack specificity in response to mechanical forces and are easily affected by multiple stimuli such as light, heat, acid and alkali in addition to mechanical forces. (2) To achieve covalent bonding with the polymer backbone, polymerizable functional groups need to be introduced into the backbone of the force-sensitive molecule. However, this modification makes its synthetic route significantly more complicated and difficult to be compatible with the mature synthetic strategies of traditional force-sensitive molecules. It usually introduces additional synthetic steps and purification steps, resulting in a complicated and costly overall process, which restricts its promotion in practical applications. (3) The color-changing properties and reversibility of most color-sensitive molecules lack tunability. They can usually only adjust the color change, but it is difficult to achieve precise control over the mechanochemical behavior such as ring-opening reaction kinetics. This is mainly because traditional mechanosensitive molecular structures often exhibit irreversible or slow mechanochromic properties, and their structural modifications usually require de novo design and synthesis, which is time-consuming and inefficient. These structural limitations not only restrict the tunability of molecules, but also make it difficult to meet the performance requirements of different application scenarios. For example, material damage detection requires mechanosensitive molecules with slow fading properties, while real-time stress detection relies on color-changing molecules that can respond instantaneously. Summary of the Invention

[0007] The purpose of this invention is to provide a mechanochromic molecule based on crystal violet lactam, its bulk polymer, and its applications, in order to solve the technical problems of insufficient specificity of existing mechanochromic molecules in response to mechanical force, complex structural modification, and complex synthetic routes.

[0008] To achieve the above objectives, the present invention provides a mechanochromic molecule based on crystal violet lactam, selected from any of the following: (1) Based on single-crystal ultraviolet lactam: (2) Based on double-crystal violet lactam: (3) Based on double-crystal violet lactam: .

[0009] Preferably, the mechanochromic molecule has the following general chemical structural formula:

[0010] More preferably, the mechanochromic molecule is selected from any one of the following: Acrylamide and acrylate-terminated crystal violet lactam derivative M1: ; Diacrylate-terminated crystal violet lactam derivative M2: ; M3, a dibromo-terminated crystal violet lactam derivative: ; Dipentenoate-terminated crystal violet lactam derivative M4: .

[0011] More preferably, M1 is prepared by the following method: (M1-1) First, 4-dimethylaminobenzaldehyde, 3-(dimethylamino)benzoic acid, urea and N-methylaniline were dissolved in 6.0 mL of concentrated hydrochloric acid, heated to 95 °C and refluxed for 12 h under a nitrogen atmosphere, and then cooled to room temperature (25 °C) for the first post-treatment to obtain compound 1; (M1-2) Then compound 1 was added to 2 mL of 2-aminoethanol, stirred under blowing air at 150 °C for 24 h, and then subjected to a second post-treatment to obtain compound 2; (M1-3) Finally, compound 2 was dissolved in dry dichloromethane, Et3N was added, acryloyl chloride was added dropwise at 0°C, and the mixture was allowed to stand and stirred for 12 h. After the third post-treatment, M1 was obtained.

[0012] More preferably, in step (M1-1), the ratio of 4-dimethylaminobenzaldehyde, 3-(dimethylamino)benzoic acid, urea, N-methylaniline, and 6M hydrochloric acid is 10 mmol: 10 mmol: 10 mmol: 10 mmol: 6 mL; in step (M1-2), the ratio of compound 1 to 2-aminoethanol is 1 mmol: 2 mL; and in step (M1-3), the ratio of compound 2, dichloromethane, Et3N, and acryloyl chloride is 0.5 mmol: 5 mL: 3 mmol: 2 mmol.

[0013] More preferably, the first post-treatment includes: adjusting the pH of the reaction solution to 10 using 0.6 M NaOH solution, washing with toluene, adjusting the pH of the water extract to 5 by adding 2 M HCl solution dropwise, precipitating, and filtering; the second post-treatment includes: cooling to room temperature, adding water, obtaining the crude product by vacuum filtration, slurrying in methanol for 1 h, precipitating, and filtering; the third post-treatment includes: quenching with water, extracting with DCM, washing with saturated NaHCO3 and brine, drying with anhydrous Na2SO4, concentrating under reduced pressure, and performing silica gel column chromatography.

[0014] More preferably, M2 is prepared by the following method: (M2-1) First, N-(2-hydroxyethyl)-N-methylaniline, DMAP and Et3N were added to dry DCM. Acetic anhydride was added dropwise at 0°C for 10 min. The mixture was then allowed to stand and stir for 2 h. After the first post-treatment, compound 3 was obtained. (M2-2) Then 4-dimethylaminobenzaldehyde, 3-(dimethylamino)benzoic acid, urea and compound 3 were dissolved in hydrochloric acid solution, heated to 95°C and refluxed for 12 h under nitrogen atmosphere, and a second post-treatment was performed to obtain compound 4. (M2-3) Compound 4 was then added to 2-aminoethanol and stirred at 150°C for 24 h. After the third post-treatment, compound 5 was obtained. (M2-4) Finally, compound 5 was dissolved in dry dichloromethane, Et3N was added, acryloyl chloride was added dropwise at 0°C, and the mixture was allowed to stand and stir for 12 h. After the fourth post-treatment, M2 was obtained.

[0015] More preferably, in step (M2-1), the ratio of N-(2-hydroxyethyl)-N-methylaniline, DMAP, Et3N, DCM, and acetic anhydride is 20 mmol: 1 mmol: 60 mmol: 100 mL: 26 mmol; in step (M2-2), the ratio of 4-dimethylaminobenzaldehyde, 3-(dimethylamino)benzoic acid, urea, compound 3, and hydrochloric acid solution is 10 mmol: 10 mmol: 10 mmol: 10 mmol: 6 mL, wherein the concentration of the hydrochloric acid solution is 6 mol / L; in step (M2-3), the ratio of compound 4 and 2-aminoethanol is 1 mmol: 2 mL; and in step (M2-4), the ratio of compound 5, dichloromethane, Et3N, and acryloyl chloride is 0.5 mmol: 5 mL: 3 mmol: 2 mmol.

[0016] More preferably, the first post-treatment includes: washing with brine, drying the organic extract on anhydrous Na₂SO₄, concentrating under reduced pressure, and silica gel column chromatography; the second post-treatment includes: cooling to room temperature, adjusting the pH of the reaction solution to 10 with 0.6 M NaOH solution, heating at 70°C for 2 h, cooling to room temperature, washing with ethyl acetate, adjusting the pH of the water extract to 5 by adding 2 M HCl solution dropwise, precipitating and extracting the crude product with ethyl acetate (10.0 mL × 3), drying the organic extract on anhydrous sodium sulfate, concentrating under reduced pressure, and silica gel column chromatography; the third post-treatment includes: cooling to room temperature, adding 40 mL of brine, extracting with DCM, drying the organic extract on anhydrous Na₂SO₄, concentrating under reduced pressure, and silica gel column chromatography; the fourth post-treatment includes: quenching with water, extracting with DCM, washing with saturated NaHCO₃ and brine, drying with anhydrous Na₂SO₄, concentrating under reduced pressure, and silica gel column chromatography.

[0017] More preferably, M3 is prepared by the following method: compound 5 is added to dry DCM, Et3N and 2-bromoisobutyryl bromide are added, the mixture is added dropwise at 0°C for 10 min, stirred for 5 h, and then post-treated to obtain the final product.

[0018] More preferably, the ratio of compound 5, DCM, Et3N, and 2-bromoisobutyryl bromide is 0.5 mmol: 5 mL: 3 mmol: 2 mmol.

[0019] More preferably, the post-processing includes: quenching with water followed by extraction with ethyl acetate, washing with saturated NaHCO3 and brine, drying with anhydrous Na2SO4, concentration under reduced pressure, and silica gel column chromatography.

[0020] More preferably, M4 is prepared by the following method: Compound 5 and DMAP are mixed in dry THF, Et3N is added, acrylic anhydride is added dropwise at 0°C for 10 min, the mixture is allowed to stand and stirred for 12 h, and then post-processed to obtain the final product.

[0021] More preferably, the ratio of compound 5, DMAP, THF, Et3N, and acrylic anhydride is 0.5 mmol: 0.025 mmol: 5 mL: 3 mmol: 2 mmol.

[0022] In a further preferred embodiment, the post-processing includes: water quenching, DCM extraction, washing with saturated NaHCO3 and brine, drying with anhydrous Na2SO4, concentration under reduced pressure, and silica gel column chromatography.

[0023] The present invention also provides a bulk polymer of the aforementioned mechanochromic molecules.

[0024] Preferably, the bulk polymer is prepared by the following method: using methyl acrylate or polymethyl acrylate- co - Using ethylene glycol acrylate as a monomer and the aforementioned methachromic molecule as a crosslinking agent, photopolymerization generates a primary polymer network (SN); swelling in a solution of methyl acrylate monomer or methyl acrylate / ethylene glycol acrylate, crosslinking agent EGDMA, and TPO, followed by photopolymerization, yields a secondary polymer network (DN); in a solution of methyl acrylate monomer or polymethyl acrylate... co - Swelling in a solution of ethylene glycol acrylate, crosslinking agent EGDMA and TPO, followed by photopolymerization, yields a triple polymer network TN.

[0025] More preferably, the mechanochromic molecule is M1 or M2.

[0026] Preferably, the bulk polymer is prepared by the following method: using the aforementioned mechanochromic molecule as an initiator, methyl methacrylate as a monomer, and Me6TREN as a ligand, a copper-catalyzed polymerization reaction is carried out under a nitrogen atmosphere to obtain a linear polymer.

[0027] More preferably, the mechanochromic molecule is M3.

[0028] Preferably, the bulk polymer is prepared by the following method: blending the aforementioned mechanochromic molecule with the Sylgard® 184 prepolymer matrix, adding a curing agent, mixing thoroughly, pouring into a mold, and curing to obtain the polymer.

[0029] More preferably, the mechanochromic molecule is M4.

[0030] This invention also provides applications of the aforementioned mechanochromic molecules in real-time stress monitoring, mechanical flaw detection visualization, information storage, or inkless writing.

[0031] The present invention has the following beneficial effects: This invention provides a mechanochromic molecule, bulk polymer, and its application based on crystal violet lactam. It organically combines the introduction process of mechanosensitive units and polymerizable functional groups, effectively simplifying the synthesis steps, reducing the preparation cost, and providing a new approach for the design of controllable and specific mechanochromic materials.

[0032] This invention achieves precise control over color and mechanochromic behavior through molecular structure optimization and polymer structure design. The molecule boasts advantages such as simple synthesis steps, inexpensive raw materials, and low cost, enabling large-scale preparation. Furthermore, it exhibits a stable and significant mechanochromic effect in polymer materials under mechanical compression or stretching, thus possessing broad application prospects.

[0033] Compared with existing spiropyran, rhodamine, and other force-sensitive molecules, the improvement of this invention lies in: (1) Since breaking the amide bond in the crystal violet lactam structure requires overcoming a high potential energy barrier, the structure is stable against various external stimuli such as light, heat, acid and alkali, and has specific mechanical selectivity. (2) By simply changing the substituents, the mechanochromatic behavior of blue with long lifetime and green with short lifetime was controlled; (3) The synthesis route is simple and can be prepared on a large scale, with low cost; (4) It exhibits excellent force-induced color change performance in triple network elastomers and PDMS, enabling real-time stress monitoring and structural damage visualization.

[0034] (5) Based on the polymer structure, regulate the interaction between the polymer and the force-sensitive molecule M1 to stabilize its force response and generate structure.

[0035] Bulk polymers containing crystal violet lactamide force-sensitive molecules undergo mechanical force transmission to the force-sensitive molecules through chain movement and deformation under tensile, compressive, and abrasive forces, resulting in a force-induced color change. This implies a correlation between the color change and the aforementioned force behavior or mechanical properties. For example, there is a correlation between stress-strain parameters and color change during tensile stress, pressure magnitude and color change during compressive stress, and wear degree and color change. Based on these relationships, the applicant has verified the application prospects of bulk polymer materials containing crystal violet lactamide force-sensitive molecules in stress detection and damage detection, information storage, and inkless writing. The following applications utilize crystal violet lactamide force-sensitive polymers in polydimethylsiloxane (PDMS) and polymethyl methacrylate (PMA) triple network elastomers and polymethyl methacrylate- co - Ethylene glycol acrylate (PMA- co -HEA) triple network. Furthermore, if crystal violet lactam force-sensitive molecules are incorporated into other polymers (such as polyethylene (PE), polypropylene (PP), polycarbonate (PC), polybutadiene (PB), polyurethane (PU), polyamide (PA), polyacrylamide (PAM), polyvinyl alcohol (PVA), polyaniline (PANI), etc.), the correlation between force-induced behavior and the mechanochromic effect remains, and these application effects can still be achieved.

[0036] In summary, this invention utilizes a crystal violet lactone / lactam-based force-sensitive molecule design. By converting the tension site on one side of the force-sensitive molecule from an amide group to an alkylamine group, the color (from green to blue) and reversibility (from fast to slow) of the mechanochromatic effect are controlled. A low-cost, scalable synthetic route (two-step method, low cost) is employed. Furthermore, this invention introduces crystal violet lactone force-sensitive molecules into various polymer materials, endowing them with mechanochromatic phenomena under mechanical actions such as tension, compression, shear, and abrasion. This phenomenon can be further applied to material damage visualization, material mechanical monitoring, material information storage, and the preparation of inkless writing materials. This invention is based on polymer structure regulation to stabilize the interaction between the polymer and the force-sensitive molecule M1, thereby altering the rate of mechanochromatic color change.

[0037] In addition to the objectives, features, and advantages described above, the present invention has other objectives, features, and advantages. The invention will now be described in further detail with reference to the figures. Attached Figure Description

[0038] The accompanying drawings, which form part of this application, are used to provide a further understanding of the invention. The illustrative embodiments of the invention and their descriptions are used to explain the invention and do not constitute an undue limitation of the invention. In the drawings: Figure 1Synthetic route of the force-sensitive molecule M1.

[0039] Figure 2 Synthetic route of the force-sensitive molecule M2.

[0040] Figure 3 Synthetic route of the force-sensitive molecule M3.

[0041] Figure 4 Synthetic route of the force-sensitive molecule M4.

[0042] Figure 5 Synthetic route for controlling molecule C1.

[0043] Figure 6 Synthetic route for controlling molecule C2.

[0044] Figure 7 Synthetic route of compound 7.

[0045] Figure 8 Schematic diagram of the fabrication of the triple network.

[0046] Figure 9 Preparation of linear polymer PMA.

[0047] Figure 10 .P 1-67k ,P 2-80k ,P 3-99k . and P 4-148k GPC diagram. Figure 11 .P con-76k GPC graph. Powerful color-changing verification. Figure 12 .M1-TN 0.2 and M1-TN 1.0 Stress-strain curve.

[0048] Figure 13 .M2-TN 0.2 Stress-strain curve.

[0049] Figure 14 .C1-TN 0.2 Stress-strain curve.

[0050] Figure 15 (a) Fabrication process of the triple network; (b) Schematic diagram of real-time detection of images and optical signals during stretching; M1-TN 1.0 (c) RGB channel changes, sample image, and (d) absorption spectrum after sample stretching; (e) stress relaxation experiment and (f) RGB channel changes after cyclic stretching.

[0051] Figure 16 M2-TN0.2 (a) Changes in RGB channels, (b) Sample image, (c) Absorption spectrum, and (d) Comparison with control C1-TN after sample stretching. 0.2 RGB channel changes in the samples compared to those in the stress relaxation experiment and the tensile fracture experiment.

[0052] Figure 17 Images of M4-PDMS before and after pressurization.

[0053] Figure 18 .M1- co TN 0.2 Images of the sample before and after tensile fracture.

[0054] Figure 19 .M1- co TN 0.2 Information displayed for the M2-TN sample after pressure was applied to the steel mold.

[0055] Figure 20 PMA polymer in acetonitrile solution (2 mg / ml) at 0 o (a) Absorption spectrum every ten minutes of the solution under C during sonication and (b) with control polymer P con (c) Intensity comparison at an absorption wavelength of 603 nm, fading kinetics at room temperature after sonication, (d) normalized intensity plots of different molecular weights (P1-P4) at an absorption wavelength of 603 nm during sonication, (e) correlation line between absorption intensity and concentration of reference molecule 7 under acid treatment, and (f) comparison of activation rate and activation rate of different molecular weights (P1-P4).

[0056] Figure 21 (a) Model molecular structures used for calculation and (b) synthesized molecular structures of force-sensitive molecules M1 and M2; CoGEF calculations were performed on model molecules M1 and M2 at the B3LYP / 6-31G (d) theoretical level and in the gas phase and acetonitrile solvent phase, respectively. Constrained geometry optimization was performed at each stretching step. For the initial equilibrium configuration, the total energy and the distance between stretching points were set to 0 kJ / mol and 0 Å, respectively.

[0057] Figure 22 (a) Configuration of model molecule M1 under restoring force (2 nN), and (b) Correlation between CN bond length and external force and effective force constant of model molecules M1 and M2 calculated by RFT. k eff(c) Resilience triangle; (d) Transition state and configuration after heterolytic cleavage of CN bond in M1 model molecule under zero force; (e) Energy of CN bond before and after heterolytic cleavage and transition state in gaseous and acetonitrile solutions of M1 and M2 model molecules; (f) Correlation diagram of free energy barrier of force coupling and external force.

[0058] Figure 23 TGA curve of component 5 and after heating 1 H NMR spectrum. TGA test was performed under nitrogen atmosphere at a heating rate of 10 K / min.

[0059] Figure 24 Photographs of P1 before and after irradiation with 405 and 365 nm wavelength light in THF (2 mg / ml) and treatment with 10 mM TFA and TEA for 30 min. Detailed Implementation

[0060] The embodiments of the present invention will be described in detail below with reference to the accompanying drawings. However, the present invention can be implemented in many different ways as defined and covered by the claims.

[0061] This invention synthesizes four force-sensitive molecules (M 1-4 This study verifies the force response characteristics, color, and controllability of reversible force-induced color change. By adjusting the characteristics of the electron-pull / electron-donating groups around the force application point, the color (blue / green) and reversibility (long / short lifetime) of the force-sensitive molecule can be controlled. Specifically, molecule M1 contains an electron-withdrawing amide group, exhibiting green under stress and fading rapidly after stress removal; molecule M2 contains an electron-donating alkylamine group, exhibiting blue under stress and fading more slowly after stress removal. Furthermore, the reversibility of the force response of molecule M1 can be controlled by adjusting the polymer structure. The nitrogen anion generated by the force response of molecule M1 forms hydrogen bonds with hydroxyl groups in the polymer matrix, thus controlling the transition from rapid to slow reversibility of the force-induced color change. Both types of molecules can be prepared through a two-step reaction at a low cost of approximately 4.5 CNY / g, currently the most inexpensive of all color-changing force-sensitive molecules. Simultaneously, the applicant has achieved large-scale preparation of force-sensitive molecules at the kilogram level. Introducing this force-sensitive molecule into polydimethylsiloxane (PDMS) and polymethyl methacrylate (PMA) triple network elastomers and polymethyl methacrylate- co - Ethylene glycol acrylate (PMA- co In the HEA triple network, real-time stress monitoring, mechanical flaw detection visualization, information storage, and inkless writing applications were realized. Finally, the applicant also verified that these force-sensitive molecules exhibit specificity in their sensitivity to mechanical forces and inertness in response to other stimuli.

[0062] 1. Synthesis of force-sensitive molecules The reactants used in the following synthesis were sourced from Adamas, except for controlled substances such as hydrochloric acid and toluene, which were sourced from Sinopharm Group. Unless otherwise specified, the reactants were used directly without processing.

[0063] Figure 1 The synthetic route for the force-sensitive molecule M1 is shown.

[0064] Compound 1: 4-Dimethylaminobenzaldehyde (1492 mg, 10.0 mmol, 1.0 equiv), 3-(dimethylamino)benzoic acid (1652 mg, 10.0 mmol, 1.0 equiv), urea (550 mg, 10.0 mmol, 1.0 equiv), and N-methylaniline (1072 mg, 10.0 mmol, 1.0 equiv) were dissolved in 6.0 mL of 6M hydrochloric acid. The reaction mixture was heated to 95°C. o Refluxed under N2 at C for 12 h, cooled to room temperature, and the pH of the reaction mixture was adjusted to 10 by adding 0.6 M NaOH solution dropwise. The reaction mixture was washed with toluene (10.0 mL × 3). The pH of the aqueous extract was adjusted to 5 by adding 2 M HCl solution dropwise. The product was precipitated and filtered to give compound 1 (2821 mg, 70%) as a white solid. 1 H NMR (400 MHz, CD3CN) δ 7.12 (d, J = 2.8 Hz,1H), 6.88 – 6.74 (m, 6H), 6.65 (d, J = 8.7 Hz, 2H), 6.48 (d, J = 8.5 Hz, 2H), 6.12 (s, 1H), 2.90 (s, 6H), 2.86 (s, 6H), 2.71 (s, 3H). 13 C NMR (151 MHz, DMSO)δ 169.74, 148.47, 147.94, 147.81, 133.14, 132.71, 132.15, 131.95, 130.87,129.50, 114.86, 113.03, 112.27, 112.25, 111.34, 48.62, 40.30, 40.09, 29.90.LC-MS: m / z found [M+H] + for C 25 H 29 N3O2404.2341 (calcd. 404.2333).

[0065] Compound 2: Compound 1 (403 mg, 1.0 mmol, 1.0 equiv) was added to 2 mL of 2-aminoethanol. The reaction mixture was heated to 150 °C. o Stirring under C for 24 h, cooling to room temperature, and adding 40 mL of water. The crude product was obtained by vacuum filtration, and then slurried in 2 mL of MeOH for 1 h. After precipitation and filtration, a white solid compound 2 (186 mg, 42%) was obtained. 1 H NMR (400MHz, CD3CN) δ 7.11 (d, J = 8.5 Hz, 1H), 7.06 – 7.02 (m, 2H), 7.01 (d, J = 2.6Hz, 1H), 6.99 – 6.92 (m, 3H), 6.73 – 6.68 (m, 2H), 6.57 – 6.53 (m, 2H), 4.50 (s, 1H), 3.49 (td, J = 6.2, 2.7 Hz, 2H), 2.98 (s, 8H), 2.92 (s, 6H), 2.75 (d,J = 5.0 Hz, 3H). 13 C NMR (151 MHz, CD2Cl2) δ 171.61, 151.28, 150.68, 149.68,140.74, 131.53, 129.53, 129.48, 129.29, 129.27, 128.44, 124.11, 117.49,112.63, 112.53, 105.95, 75.92, 62.93, 45.97, 41.17, 40.74, 30.95. LC-MS: m / zfound [M+H] + for C 27 H 32 N4O2445.2612 (calcd. 445.2598).

[0066] Mechanosensitive molecule M1: Compound 2 (244 mg, 0.50 mmol, 1.0 equiv) was dissolved in 5.0 mL of dry dichloromethane (DCM), and Et3N (416 μL, 3.0 mmol, 6.0 equiv) was added. oUnder C conditions, acryloyl chloride (163 μL, 2.0 mmol, 4.0 equiv) was added dropwise, and the mixture was allowed to stand with stirring for 12 h. After quenching the reaction with water, the mixture was extracted with DCM (15 mL × 3). The product was washed with saturated NaHCO3 (20 mL × 2) and brine (20 mL × 2), dried over anhydrous Na2SO4, and concentrated under reduced pressure. The crude product was subjected to silica gel column chromatography with a gradient eluent (60:40 PE / EtOAc, v / v) to obtain a pale yellow solid, the force-sensitive molecule M1 (244 mg, 82%). 1 H NMR (400 MHz, CD3CN) δ 7.35 – 7.27 (m, 2H), 7.23 – 7.12 (m, 3H), 7.05– 6.91 (m, 4H), 6.69 (d, J = 8.9 Hz, 2H), 6.28 – 6.07 (m, 3H), 5.96 (dd, J =17.3, 10.5 Hz, 1H), 5.79 (dd, J = 10.5, 1.6 Hz, 1H), 5.54 – 5.46 (m, 1H), 3.83– 3.74 (m, 1H), 3.66 – 3.46 (m, 3H), 3.25 (s, 3H), 2.98 (s, 6H), 2.91 (s, 6H). 13 C NMR (151 MHz, CD3CN) δ 169.73, 166.33, 165.86, 152.00, 151.38, 143.99,142.35, 139.80, 132.11, 131.46, 129.91, 129.71, 129.14, 128.29, 128.26,127.37, 124.83, 113.04, 105.78, 75.17, 61.70, 40.88, 40.56, 40.49, 40.36,37.48. LC-MS: m / z found [M+H] + for C 33 H 36 N4O4553.2807 (calcd. 553.2809).

[0067] Figure 2 The synthetic route for the force-sensitive molecule M2 is shown.

[0068] Compound 3: Add to 100 mL of dry DCM N -(2-hydroxyethyl)- N-Methylaniline (3024 mg, 20.0 mmol, 1.0 equiv), DMAP (122 mg, 1.0 mmol, 0.05 equiv), and Et3N (8324 μL, 60.0 mmol, 3.0 equiv). In 0 o Under C conditions, acetic anhydride (2439 μL, 26.0 mmol, 1.3 equiv) was added dropwise for 10 min, and the mixture was allowed to stand with stirring for 2 h. The extract was then washed with saturated saline (100 mL × 3). The organic extract was dried over anhydrous Na₂SO₄ and concentrated under reduced pressure. The crude product was subjected to silica gel column chromatography with a gradient eluent (90:10 PE / EtOAc, v / v) to give a colorless liquid compound 3 (3667 mg, 95%). 1 H NMR (600 MHz, CD3CN) δ 7.19 (dd, J = 8.8, 7.2 Hz, 2H), 6.75 (dd, J = 7.9, 1.5 Hz, 2H), 6.65 (d, J = 1.1 Hz, 1H), 4.20 (t, J = 5.9 Hz, 2H), 3.57 (t, J = 5.9 Hz, 2H), 2.93 (s, 3H), 1.93 (s, 3H). 13 C NMR (151 MHz, CD3CN) δ 171.67, 150.27, 130.06, 117.21, 113.15, 62.22, 51.67, 38.93, 21.03.LC-MS: m / z found [M+H] + for C 11 H 16 NO2194.1182 (calcd. 193.1176).

[0069] Compound 4: 4-Dimethylaminobenzaldehyde (1492 mg, 10.0 mmol, 1.0 equiv), 3-(dimethylamino)benzoic acid (1652 mg, 10.0 mmol, 1.0 equiv), urea (550 mg, 10.0 mmol, 1.0 equiv), and compound 3 (1931 mg, 10.0 mmol, 1.0 equiv) were dissolved in 6.0 mL of 6 M HCl. The reaction solution was heated to 95°C. o Reflux with N2 at C for 12 h, cool to room temperature, and adjust the pH of the reaction solution to 10 by adding 0.6 M NaOH solution dropwise. The mixed solution is then heated at 70°C. oThe mixture was heated at C for 2 h, then cooled to room temperature and washed with ethyl acetate (10.0 mL × 3). The pH of the aqueous extract was adjusted to 5 by adding 2 M HCl solution dropwise. The crude product was extracted with ethyl acetate (10.0 mL × 3). The organic extract was dried over anhydrous sodium sulfate and concentrated under reduced pressure. The crude product was subjected to silica gel column chromatography with a gradient elution buffer (95:5 DCM / MeOH, v / v) to give compound 4 (2236 mg, 50%) as a white solid. 1 H NMR (400 MHz, CD3CN) δ 7.12 (d, J = 2.9 Hz,1H), 6.89 – 6.79 (m, 6H), 6.68 – 6.61 (m, 4H), 6.14 (s, 1H), 3.62 (t, J = 6.1Hz, 2H), 3.37 (t, J = 6.1 Hz, 2H), 2.90 (d, J = 1.7 Hz, 9H), 2.86 (s, 6H). 13 CNMR (151 MHz, DMSO- d 6) δ 169.76, 148.51, 147.99, 147.17, 133.07, 132.62,132.09, 131.94, 130.90, 129.60, 129.51, 114.91, 113.08, 112.28, 111.39,58.17, 54.92, 54.40, 48.51, 40.31, 40.10, 38.63. LC-MS: m / z found [M+H] + forC 27 H 33 N3O3448.2581 (calcd. 448.2595).

[0070] Compound 5: Compound 4 (447 mg, 1.0 mmol, 1.0 equiv) was added to 2 mL of 2-aminoethanol. 150 o After stirring at C for 24 h, the mixture was cooled to room temperature and 40 mL of saturated saline solution was added. Extraction was performed using DCM (10.0 mL × 3). The organic extract was dried over anhydrous Na₂SO₄ and concentrated under reduced pressure. The crude product was subjected to silica gel column chromatography with a gradient elution buffer (20:80 PE / EtOAc, v / v) to give compound 5 (254 mg, 52%) as a white solid. 1H NMR (600 MHz, CD3CN) δ 7.09 (d,J = 8.5 Hz, 1H), 7.05 – 6.96 (m, 5H), 6.91 (dd, J = 8.5, 2.6 Hz, 1H), 6.70 –6.65 (m, 4H), 3.62 (d, J = 6.4 Hz, 2H), 3.48 (t, J = 6.2 Hz, 3H), 3.41 (t, J= 6.0 Hz, 2H), 2.96 (s, 8H), 2.93 (s, 3H), 2.90 (s, 6H). 13 C NMR (151 MHz, CD2Cl2) δ 171.45, 151.13, 150.54, 149.85, 140.54, 131.38, 129.25, 129.20,128.67, 128.18, 123.94, 117.31, 112.63, 112.45, 105.79, 75.66, 62.82, 60.40,55.37, 45.86, 41.01, 40.57, 38.95. LC-MS: m / z found [M+H] + forC 29 H 36 N4O3489.2883 (calcd. 489.2860).

[0071] The force-sensitive molecule M2: Following the synthesis of compound M1, the reactants were compound 5 (244 mg, 0.50 mmol, 1.0 equiv), Et3N (416 μL, 3.0 mmol, 6.0 equiv), and acryloyl chloride (163 μL, 2.0 mmol, 4.0 equiv). The crude product was subjected to silica gel column chromatography with a gradient elution buffer (60:40 PE / EtOAc) to obtain a white solid force-sensitive molecule M2 (244 mg, 82%). 1H NMR (600 MHz, CD3CN) δ 7.08 (d, J = 8.5 Hz, 1H), 7.03 –6.99 (m, 4H), 6.97 (d, J = 2.6 Hz, 1H), 6.90 (dd, J = 8.6, 2.6 Hz, 1H), 6.68(dd, J = 14.1, 8.7 Hz, 4H), 6.24 (ddd, J = 17.4, 13.3, 1.5 Hz, 2H), 6.06 (dd,J = 17.3, 10.4 Hz, 1H), 5.94 (dd, J = 17.3, 10.5 Hz, 1H), 5.79 (ddd, J =17.5, 10.5, 1.5 Hz, 2H), 4.27 (t, J = 5.7 Hz, 2H), 3.63 (dt, J = 15.8, 6.2Hz, 4H), 3.57 (dd, J = 6.6, 1.8 Hz, 2H), 2.95 (s, 6H), 2.93 (s, 3H), 2.89 (s,6H). 13 C NMR (151 MHz, CD3CN) δ 169.77, 166.74, 166.42, 151.82, 151.24, 149.68,141.12, 132.10, 131.62, 131.34, 129.75, 129.70, 129.48, 129.38, 129.29,129.25, 124.79, 117.88, 113.11, 112.89, 112.87, 105.78, 75.17, 62.55, 61.93,51.47, 41.01, 40.61, 40.37, 38.89. LC-MS: m / z found [M+H] + forC 35 H 40 N4O5597.3104 (calcd. 597.3071).

[0072] Figure 3 The synthetic route for the force-sensitive molecule M3 is shown.

[0073] Mechanosensitive molecule M3: Compound 5 (244 mg, 0.50 mmol, 1.0 equiv) was added to 5.0 mL of dry DCM, followed by Et3N (416 μL, 3.0 mmol, 6.0 equiv). 2-Bromoisobutyryl bromide (247 μL, 2.0 mmol, 4.0 equiv) was added to 0 mL of dry DCM. o Add the solution dropwise for 10 min under C conditions, let it stand and stir for 5 h, quench the reaction with water, and extract with ethyl acetate (15 mL × 3). Wash with saturated NaHCO3 (20 mL × 2) and brine (20 mL × 2), dry with anhydrous Na2SO4, and concentrate under reduced pressure. The crude product was subjected to silica gel column chromatography with a gradient elution buffer (80:20 PE / EtOAc, v / v) to give a white solid, the force-sensitive molecule M3 (314 mg, 80%). 1 H NMR (600 MHz, CD3CN) δ 7.08 (d, J = 8.5 Hz, 1H), 7.05 – 7.00 (m,4H), 6.97 (d, J = 2.5 Hz, 1H), 6.91 (dd, J = 8.6, 2.6 Hz, 1H), 6.73 – 6.66(m, 4H), 4.29 (t, J = 5.4 Hz, 2H), 3.72 – 3.61 (m, 4H), 3.48 – 3.40 (m, 2H), 2.95 (d, J = 3.8 Hz, 8H), 2.90 (s, 6H), 1.84 (d, J = 1.2 Hz, 6H), 1.79 (d, J= 5.2 Hz, 6H). 13 C NMR (151 MHz, CD3CN) δ 172.31, 171.85, 169.81, 151.80,151.26, 149.66, 141.10, 132.04, 129.72, 129.71, 129.40, 129.25, 124.75,117.93, 113.15, 113.01, 105.77, 75.03, 64.40, 63.45, 57.70, 57.48, 51.08,41.01, 40.64, 39.64, 38.89, 30.97, 30.95, 30.90. LC-MS: m / z found [M+H] + forC 37 H 46 Br2N4O5785.1935 (calcd. 785.1905).

[0074] Figure 4 The synthetic route for the force-sensitive molecule M4 is shown.

[0075] Mechanosensitive molecule M4: Compound 5 (244 mg, 0.50 mmol, 1.0 equiv) was added to a mixture with DMAP (3 mg, 0.025 mmol, 0.05 equiv) in 5.0 mL of dry THF, followed by Et3N (416 μL, 3.0 mmol, 6.0 equiv). o Under C conditions, acrylic anhydride (230 μL, 2.0 mmol, 4.0 equiv) was added dropwise for 10 min, and the mixture was allowed to stand with stirring for 12 h. After quenching the reaction with water, the product was extracted with DCM (15 mL × 3). The product was washed with saturated NaHCO3 (20 mL × 2) and brine (20 mL × 2), dried over anhydrous Na2SO4, and concentrated under reduced pressure. The crude product was subjected to silica gel column chromatography with a gradient eluent (60:40 PE / EtOAc, v / v) to obtain a white solid, the force-sensitive molecule M4 (261 mg, 80%). 1 H NMR (400 MHz, CD3CN) δ 7.07 (d, J =8.7 Hz, 1H), 7.03 – 6.95 (m, 5H), 6.90 (dd, J = 8.6, 2.6 Hz, 1H), 6.70 – 6.64(m, 4H), 5.83 – 5.73 (m, 2H), 5.04 – 4.91 (m, 4H), 4.19 (t, J = 5.7 Hz, 2H), 3.58 (q, J = 6.4, 5.9 Hz, 4H), 3.49 – 3.44 (m, 2H), 2.96 (s, 6H), 2.92 (s, 3H), 2.89 (s, 6H), 2.31 – 2.23 (m, 4H), 2.21 (t, J = 1.6 Hz, 4H).

[0076] Figure 5 To control the synthetic route of molecule C1.

[0077] Compound 6: Crystal violet lactone (CVL 416 mg, 1.0 mmol, 1.0 equiv) was added to 2 mL of ethanolamine. The reaction mixture was stirred at 180 ºC for 12 h. After the reaction was complete, the mixture was cooled to room temperature and 40 mL of saturated brine was added. The mixture was extracted with dichloromethane (DCM, 10.0 mL × 3), the organic layers were combined, dried over anhydrous sodium sulfate, and concentrated under reduced pressure. The crude product was separated by silica gel column chromatography (eluent: PE / EtOAc = 20:80, v / v) to give compound 6 as a white solid (321 mg, 70% yield). 1 H NMR (400 MHz, CD3CN) δ 7.08 (d, J = 8.5 Hz,1H), 7.03 – 6.98 (m, 5H), 6.91 (dd, J = 8.5, 2.6 Hz, 1H), 6.70 – 6.65 (m,4H), 3.48 (t, J = 6.2 Hz, 2H), 3.42 (t, J = 5.5 Hz, 1H), 2.96 (s, 8H), 2.90(s, 12H). 13 C NMR (151 MHz, CD2Cl2) δ 171.45, 151.12, 150.52, 140.60, 131.39,129.17, 128.28, 123.94, 117.32, 112.45, 105.79, 75.70, 62.83, 54.20, 54.02,53.84, 53.66, 53.48, 45.86, 41.02, 40.58. LC-MS: m / z found [M+H] + forC 28 H 34 N4O2459.2778 (calcd. 459.2755).

[0078] Control molecule C1: This compound was prepared using the same synthetic method as compound M1, but with compound 6 (92 mg, 0.2 mmol, 1.0 equiv), Et3N (166 μL, 1.2 mmol, 6.0 equiv), and acryloyl chloride (65 μL, 0.8 mmol, 4.0 equiv) as starting materials. The crude product was separated by silica gel column chromatography (eluent: PE / EtOAc = 60:40, v / v) to obtain control molecule C1 as a white solid (74 mg, 72% yield). 1H NMR (600 MHz, CD3CN) δ 7.08 (d, J =8.5 Hz, 1H), 7.04 – 7.00 (m, 4H), 6.97 (d, J = 2.5 Hz, 1H), 6.91 (dd, J =8.5, 2.6 Hz, 1H), 6.69 – 6.65 (m, 4H), 6.23 (dd, J = 17.3, 1.5 Hz, 1H), 5.95 (dd, J = 17.3, 10.5 Hz, 1H), 5.78 (dd, J = 10.5, 1.5 Hz, 1H), 3.65 (t, J =6.7 Hz, 2H), 3.55 (t, J = 6.7 Hz, 2H), 2.96 (s, 6H), 2.89 (s, 12H). 13 C NMR(151 MHz, CD3CN) δ 169.77, 166.41, 151.80, 151.21, 141.14, 132.10, 131.34,129.69, 129.67, 129.42, 129.30, 124.79, 117.88, 113.12, 113.09, 105.78,75.21, 61.93, 41.01, 40.62, 40.36. LC-MS: m / z found [M+H] + forC 31 H 36 N4O3513.2884 (calcd. 513.2860).

[0079] Figure 6 To control the synthetic route of molecule C2.

[0080] Control molecule C2: This compound was prepared using the same synthetic method as compound M3, but with compound 6 (92 mg, 0.2 mmol, 1.0 equiv), Et3N (166 μL, 1.2 mmol, 6.0 equiv), and 2-bromoisobutyryl bromide (99 μL, 0.8 mmol, 4.0 equiv) as starting materials. The crude product was separated by silica gel column chromatography (eluent: PE / EtOAc = 80:20, v / v) to obtain control molecule C2 as a white solid (91 mg, 75% yield). 1H NMR (400 MHz, CD3CN) δ 7.09(d, J = 8.5 Hz, 1H), 7.05 – 7.01 (m, 4H), 6.97 (d, J = 2.4 Hz, 1H), 6.91 (dd,J = 8.5, 2.6 Hz, 1H), 6.70 – 6.66 (m, 4H), 3.68 (t, J = 6.7 Hz, 2H), 3.42 (t,J = 6.7 Hz, 2H), 2.95 (s, 6H), 2.89 (s, 12H), 1.83 (s, 6H). 13 C NMR (151 MHz, CD3CN) δ 171.86, 169.82, 151.79, 151.26, 141.12, 132.05, 129.65, 129.32,124.73, 117.90, 113.16, 105.76, 75.07, 63.47, 57.70, 41.00, 40.63, 39.63,30.89. LC-MS: m / z found [M+H] + for C 32 H 39 BrN4O3607.2303 (calcd. 607.2303).

[0081] Figure 7 The synthetic route for compound 7 is shown below.

[0082] Compound 7: Compound 4 (224 mg, 0.50 mmol, 1.0 equiv) and ammonium molybdate ((NH4)2MoO4, 20 mg, 0.10 mmol, 0.2 equiv) were added to 0.5 M NaOH solution (5.0 mL). The reaction mixture was stirred at 90 ºC, and 10% hydrogen peroxide solution (1.5 mL) was added dropwise over 12 h. After the reaction was complete, the mixture was extracted with dichloromethane (10 mL × 3), the organic phases were combined, dried over anhydrous sodium sulfate, and concentrated under reduced pressure. The crude product was purified by silica gel column chromatography (eluent: PE / EtOAc = 50:50, v / v) to give compound 7 as a white solid (134 mg, 60% yield). 1H NMR (600 MHz, CD3CN) δ 7.36 (d, J = 8.5 Hz, 1H), 7.14 – 7.04 (m, 5H), 7.02(s, 1H), 6.71 – 6.64 (m, 4H), 3.62 (q, J = 5.8 Hz, 2H), 3.41 (t, J = 6.2 Hz, 2H), 2.93 (s, 3H). 13 C NMR (151 MHz, CD3CN) δ 171.44, 152.46, 151.46, 150.36,141.85, 130.36, 129.86, 128.85, 128.74, 127.26, 125.29, 119.93, 112.81,112.37, 106.91, 92.89, 59.88, 55.26, 40.90, 40.60, 39.17. LC-MS: m / z found [M+H] + for C 27 H 31 N3O3446.2457 (calcd. 446.2438).

[0083] The applicant further scaled up the synthesis of compound 1 to 1 kg. The feed ratios remained the same as in the previous small-scale synthesis, but the feed amounts were increased to 4-dimethylaminobenzaldehyde (372 g, 2.5 mol, 1.0 equiv), 3-(dimethylamino)benzoic acid (413 g, 2.5 mol, 1.0 equiv), urea (138 g, 2.5 mol, 1.0 equiv), and... N -Methylaniline (268 g, 2.5 mol, 1.0 equiv). The reaction was carried out in a glass reactor with mechanical stirring and heating via a water bath jacket. After the reaction was complete, 50% of the product was obtained. Compared to small-scale synthesis, the yield of this reaction was slightly lower due to the lower thermal conductivity of the reactor, resulting in poorer conversion of the reactants. This large-scale synthesis validates the feasibility of the production process for compound 1. The preparation of compound 1 is the most crucial step in the synthesis of crystal violet sensitizer molecules, which is beneficial for subsequent large-scale production.

[0084] 2. Polymer Preparation In the polymer preparation process, polymerizable functional groups are effectively used to integrate force-sensitive molecules into the polymer backbone. The preparation of a polymethyl methacrylate (PMA) triple network involves integrating force-sensitive molecules M1 and M2 as crosslinking agents into the first network, ultimately forming a triple network (M1-TN). 1.0M1-TN 0.2 and M2-TN 0.2 Polymethyl acrylate-co-ethylene glycol acrylate (PMA-) was prepared using the same method. co -HEA) Triple Network (M1- co TN 0.2 For M1-TN 0.2 and M2-TN 0.2 The mass content of the force-sensitive molecule in the material is less than 0.05%. This content is lower than the mass content of the force-sensitive molecule in most reported methemochromic materials (>0.1%). Linear PMA preparation utilizes the force-sensitive molecule M3 as an initiator to undergo atom transfer radical polymerization, generating PMA chains on both sides, ultimately obtaining linear PMA (P3) with the force-sensitive molecule at the center. 1-4 PDMS is prepared by reacting the olefin of the M4 mechanosensitive molecule with silane under platinum catalysis to form a network structure (M4-PDMS).

[0085] 2.1 Preparation of polymethyl methacrylate triple network (using M1-TN) 0.2 (For example) A schematic diagram of the triple network fabrication is shown below. Figure 8 .

[0086] Single polymer network (SN): Methyl acrylate was filtered through alkaline alumina to remove inhibitors (≤100 ppm of monomethyl ether hydroquinone) before use. SN was prepared by photopolymerization at 365 nm using monomer MA (1.0 equiv), crosslinking agent M1 (0.002 equiv), and photoinitiator diphenyl (2,4,6-trimethylbenzoyl)phosphine oxide (TPO) (0.001 equiv). The mixed solution was injected into a glass mold and exposed to 405 nm light. Polymerization was then allowed to proceed for 3 minutes. The cured SN sample was then heated to 60 °C. o Vacuum at C for 12 h to remove unreacted MA.

[0087] The dual polymer network (DN): Before use, the crosslinking agent ethylene glycol dimethacrylate (EGDMA) was filtered through alkaline alumina to remove inhibitors (≤100 ppm of monomethyl hydroquinone). The SN sample swelled for 2 h in a solution of monomer MA (1.0 equiv), crosslinking agent EGDMA (0.0004 equiv), and TPO (0.001 equiv). The swollen SN was irradiated under 365 nm light for 1 h to obtain the DN sample. The DN sample was then subjected to 60... o Vacuum at C for 12 h to remove unreacted MA.

[0088] Triple polymer network (TN): The triple network was prepared using the exact same swelling-photoinitiated polymerization experimental conditions as in the DN preparation process. The final result was M1-TN. 0.2 sample.

[0089] Table 1 shows the SN preparation ratio of the PMA triple network.

[0090] Table 1. SN preparation ratio of PMA triple network Note: DNs / TNs were prepared under the same conditions.

[0091] 2.2 Polymethyl methacrylate - co - Ethylene glycol acrylate (PMA- co -HEA) Triple Network Preparation: The preparation method is the same as that for polymethyl acrylate triple network, but the monomer used is (MA:HEA, 10:1, mol / mol).

[0092] Table 2 shows PMA- co - SN preparation ratio of HEA triple network.

[0093] Table 2. PMA- co -SN preparation ratio of HEA triple network 2.3 Preparation of the polydimethylsiloxane (PDMS) network: 10 mg of the methyl ether molecule M4 dissolved in toluene (100 mg / ml) was blended with Sylgard® 184 prepolymer matrix (1000 mg), followed by the addition of a curing agent (100 mg) (prepolymer:curing agent, 10:1 (w / w)). When the prepolymer matrix and curing agent were thoroughly mixed, the mixture was poured into a PTFE mold and heated to 70°C. o Cured in a vacuum oven at C for 12 h. Finally, M4-PDMS samples were obtained.

[0094] 2.4 Linear polymer PMA ( Figure 9Before use, methyl methacrylate was filtered through an alkaline alumina column to remove polymerization inhibitors (≤100 ppm p-methoxyphenol). Initiator M3 (11.8 mg, 0.015 mmol), dimethyl sulfoxide (DMSO, 1.25 mL), methyl methacrylate (MA, 1.25 mL, 13.9 mmol), and ligand Me6TREN (20 μL, 0.075 mmol) were sequentially added to a pre-dried 25 mL Schlenk reaction flask (with a pre-installed magnetic stir bar). After sealing the flask, three freeze-thaw cycles were performed to remove oxygen. During the freezing phase of the final cycle, a freshly ground and cut copper wire (12 mm long, 8 mm in diameter) was rapidly added to the system under nitrogen protection. The flask was resealed, and after completing the remaining cycles, nitrogen was introduced. The system was stirred at room temperature for 2 h. After the reaction was complete, the flask was opened to expose to air to terminate the reaction, and the mixture was diluted with dichloromethane (DCM). The resulting solution was filtered through a short, basic alumina column covered with diatomaceous earth to remove copper, and then concentrated under reduced pressure. The crude polymer was dissolved in a small amount of DCM and then slowly precipitated by dropwise addition to methanol cooled in liquid nitrogen, repeated three times. The resulting yellow viscous substance was dried under vacuum to give 780 mg of the bromine-terminated polymer P. 1-67k ,P 2-80k ,P 3-99k . and P 4-148k The yield was 65%, see Table 3 for details, and the GPC chart is shown below. Figure 10 , Figure 11 .

[0095] Table 3. List of prepared linear PMAs 3. Force-based color-changing verification 3.1 Mechanical property testing: Uniaxial tensile, cyclic loading, and stress relaxation tests were all conducted using a uniaxial universal testing machine (CARE, ITBC-300SL). The specimens were dumbbell-shaped sheets (total length 35 mm; narrow section width 2.0 mm; thickness approximately 1.0 mm), with a gauge length L0 = 20 mm and an effective cross-sectional area A0 = ~2.0 mm². All tests were conducted at 20 ± 2 ℃ and 55 ± 5% relative humidity. The loading rate was 1 mm / s. - ¹(corresponding to an engineering strain rate of 0.1 s⁻¹ when the gauge length is 20 mm) -¹). During the experiment, force and displacement data were acquired at 10 Hz. The calculation formulas for engineering stress and strain are: σ = F / A0 and ε = ΔL / L0, respectively, where σ is stress (MPa); F is force (N); A0 is the effective cross-sectional area of ​​the sample (mm²); ε is strain (dimensionless); ΔL is elongation (mm); and L0 is the initial length (mm). Young's modulus was obtained by linear fitting of the stress-strain curve within the strain range of 0–5%. The results are shown in Table 4 and [Table data would be inserted here]. Figures 12-14 .

[0096] Table 4. Mechanical Properties In the cyclic tensile test, the specimen was subjected to a tensile test at 1 mm·s. - ¹ Twenty-one loading-unloading cycles were performed at a rate of 1 mm·s⁻¹, with a strain range of 0–100%. In the stress relaxation experiment, the specimen was subjected to a rate of 1 mm·s⁻¹. - ¹ The stress is stretched at the target strain and then kept constant, and the stress decay process over time is recorded.

[0097] 3.2 Optical Recording and Image Analysis: Throughout all mechanical experiments, a CCD camera (Irayple, A7500CU35) was used to record the color changes of the samples in real time, capturing one image every 0.5 seconds. The resulting images were processed using ImageJ software, and a fixed region of interest (ROI) was selected to extract the average intensity values ​​of the red, green, and blue (RGB) channels for quantitative analysis of color changes.

[0098] During stretching, UV-vis spectra were collected using a PEG2000 spectrometer from Fuxiang.

[0099] 3.3 Solution ultrasonic and absorption spectroscopy monitoring: The ultrasonic experiments were conducted using a Vibra Cell VCX500 liquid processor from Sonics & Materials, equipped with a 0.5-inch (13 mm) diameter, 10-inch (254 mm) full-wave solid-state probe (part number: 630-0217), a probe adapter (part number: 830-00014), and a 50 mL three-necked Suslick reaction flask (part number: 830-00011) custom-made by Qinbo Glass Instruments. The entire ultrasonic system was housed in a soundproof enclosure (part number: 830-00427) to reduce high-frequency noise. The reaction flask was immersed in an ethanol bath in an outer beaker containing an 80% ethylene glycol aqueous solution as coolant, and equipped with a JOANLAB MS5 magnetic stirrer. The coolant was circulated through an EYELA CCA-1112A circulating cooler to maintain the ethanol bath temperature at 0 °C (unless otherwise specified).

[0100] The polymer solution was pumped from the reaction flask to a quartz flow cell (part numbers: 6610020200 and 6610023700, Agilent Technologies) using a Kamor LLS PLUS-B163 peristaltic pump and detected on an Agilent Cary 60 UV-Vis and Agilent Cary fluorescence spectrometer. The entire flow system was connected using PEEK tubing (inner diameter × outer diameter: 0.75 × 1.60 mm) and PTFE fittings (part numbers: AA-1, BB-1, WZ-32L-PTFE) supplied by Runze Fluid Control Equipment.

[0101] 3.4 Mechanochromic effect of polymers: M1-TN 1.0 The sample exhibited a distinct green color during stretching, but faded rapidly after tensile fracture. Similarly, it showed a force-induced color change effect that rapidly correlated with stress during stress relaxation and cyclic tensile tests.

[0102] M1- co TN 0.2 The sample exhibited a distinct green color both during stretching and after fracture. This result demonstrates the mechanochromic effect of the polymer structure regulating the force-sensitive molecule M1. This is because the interaction between the polymer's side-group hydroxyl functional groups and the nitrogen anions in the open-ring structure stabilizes the open-ring structure.

[0103] M2-TN 0.2 The samples exhibit significant color changes under both tension and compression. Under uniform uniaxial tension, the color change is correlated with stress-strain, revealing the history of force application.

[0104] M1- co TN 0.2 The sample did not show obvious color change when stretched, but showed obvious color change when compressed.

[0105] The linear polymers PMA (P1-P4) achieved significant mechanochromic effects in acetonitrile solutions via ultrasound.

[0106] 5. Applications of stress detection and damage detection The mechanochemical activation behavior of the force-sensitive molecule M1 was investigated in the TN material platform and verified using in-situ RGB analysis. Specifically, M1 was introduced into the first network of the TN material, resulting in M1-TN (Figure 15a). The material changes from colorless to green under stress (tension or compression), and rapidly returns to colorless upon relaxation. Uniaxial tensile experiments combined with real-time RGB image analysis showed that the change in the green / red (G / R) signal ratio was the most significant (Figures 15b-c). At fracture, the stress-strain rapidly relaxed and recovered, and the green color immediately faded, confirming the ultrafast reversibility of this force-induced ring-opening process. Only a small amount of color residue remained, presumably due to interaction with ambient humidity. The influence of humidity and environmental factors on its stability will be explored in subsequent studies. This project aims to stabilize the ring-opening structure of M1 by controlling the polymer structure (e.g., adjusting PMA to PHEA).

[0107] In the static stress relaxation experiment, the sample was held at a fixed strain (ε = 1). The results showed rapid stress relaxation, and the G / R ratio recovered to 75% of its original value (Fig. 15d), further verifying that the M1-TN sample has a rapid and reversible mechanochemical activation pathway. Further UV-Vis spectral analysis also confirmed this phenomenon. A characteristic absorption peak at 644 nm appeared at strain ε = 1 (Fig. 15e). After the stress was removed, the absorption peak decreased rapidly.

[0108] To further investigate the rapid and reversible mechanochromic behavior of the M1 force-sensitive molecule, cyclic tensile tests were conducted on the M1-TN sample. In the cyclic tensile tests, the sample was repeatedly loaded and unloaded at a strain of 1. The results showed that the G / R ratio increased during loading and decreased during unloading; when the stress returned to zero, the recovery rate of the G / R ratio exceeded 75%. However, due to the strain hysteresis effect of the elastic matrix, the peak G / R signal intensity gradually decreased in the second and subsequent cycles.

[0109] A uniaxial tensile test was performed on M2-TN, and color changes were recorded at 500 ms intervals against a white light background using a high-resolution camera (Fig. 16b). The resulting images were analyzed using ImageJ software, with a fixed region of interest (ROI) to extract signals from the RGB channels. The results showed that the blue / red (B / R) signal ratio increased significantly under strain (Fig. 16a). As the tensile length increased, the sample gradually turned blue, the mechanism of which was force-induced C–N bond breakage, generating a triarylmethyl cation (Fig. 16b). Further UV–Vis spectral analysis also verified this phenomenon. A characteristic absorption peak at 603 nm appeared at a strain ε = 3 (Fig. 16c). After relaxation, the absorbance increased, attributed to the increase in sample thickness, consistent with the structural recovery process. According to RGB channel analysis, the threshold activation strain of M2-TN was approximately 1.3. In contrast, the control sample did not show any color change (Fig. 16d), further demonstrating the force-induced color change. Furthermore, when the sample was held at strain ε = 3, stress relaxation occurred, while the B / R ratio remained essentially stable, indicating the stability of the force-induced chromogenic structure (Figure 16e). Finally, reversible kinetic analysis of the fractured sample showed a half-life of 1.5 h calculated based on the B / R ratio, indicating that the material can retain a visual record of mechanical forces for a certain period of time.

[0110] A pressure test was performed on the M4-PDMS sample. After pressure was applied, the damaged area showed a distinct blue color (…). Figure 17 This demonstrates that the force-sensitive molecules endow the PDMS material with the ability to display destructive damage. After two days, the sample had largely faded, indicating its good recovery ability.

[0111] To control the mechanochromic effect and application scenarios on demand by modulating the polymer structure using the mechanosensitive molecule M1. A PMA- co -HEA Triple Network (M1- co TN 0.2 The interaction of the hydroxyl functional group with nitrogen anions stabilizes the structure of the product after force response, enhancing its mechanochromic effect and extending the retention time of the color change. This allows the force-sensitive molecule M1 to achieve the same application as M2 in recording the history of force application and damage. During stretching, M1- co TN 0.2 The sample showed a distinct green color both before and after fracture. Figure 18Similarly, based on the mechanism by which the interaction between the polymer and the mechanosensitive molecule enhances the mechanochromic effect, the applicant hypothesizes that polymer structures containing hydrogen donor functional groups can achieve this effect. Therefore, for the mechanosensitive molecule M1, polymers such as polyurethane (PU), polyamide (PA), polyacrylamide (PAM), polyvinyl alcohol (PVA), and polyaniline (PANI) can also modulate the mechanochromic effect.

[0112] 6. Information storage and inkless writing applications Handle the steel mold (FUDAN) sequentially to M1- co TN 0.2 After pressurizing the M2-TN sample, obvious color traces (FUDAN) were observed in the sample. Figure 19 Furthermore, this distinct color can be maintained for more than 12 hours, indicating that the sample has the ability to preserve information. In addition, after 24 hours, the color on the sample has basically disappeared, and it can be used again for information recording.

[0113] After the M2-TN sample had completely faded, an inkless writing application was performed. The applicant wrote an "X" on it with tweezers, and the writing was clearly visible. Figure 19 ).

[0114] 7. Solution sonication experiment A polymer solution (2 mg / mL, acetonitrile solvent) containing the M3 mechanosensitive molecule at the center of the chain was sonicated at 0 °C (1 s on / 1 s off, sound intensity 9.7 W / cm²), and simultaneously circulated into a UV-Vis spectrometer for in-situ monitoring. The results showed that the polymer P1 (Mn = 67 kDa, The solution (Mn = 1.15) gradually changed from colorless to blue. Real-time UV-Vis spectroscopy showed that the absorption peak at 603 nm gradually increased over time under ultrasonic treatment (Fig. 20a). As a control, the polymer Pcon (Mn = 82 kDa) containing the control molecule C1 at the end was used. = 1.22) No color or spectral change was observed (Fig. 20b), indicating that the observed coloration originated from the mechanical force transmitted by cavitation collapse, rather than thermal effects or other external factors.

[0115] After 3 h of sonication, the solution was placed in a dark environment at room temperature for kinetic analysis of fading. The results showed a half-life of 20.3 h (Figure 20c). The obtained absorption spectrum was compared with the spectrum of the CVL model compound triggered by acetic acid ring opening. The results showed a high degree of overlap, verifying that the chromogenic species was a triarylmethyl cation.

[0116] To investigate the effect of molecular weight on the mechanochemical activation rate and efficiency, a series of polymers with different molecular weights, P1–P4 (67–148 kDa), were synthesized and experiments were conducted under ultrasonic conditions, with their UV–Vis absorption spectra monitored in real time. The absorbance data at 603 nm were fitted using an exponential growth model to extract the apparent mechanochemical rate constant. k obs The results showed that the kobs of P1–P4 (67, 80, 99, and 148 kDa) increased with increasing molecular weight, with the rate constant of P4 being 3.9 times higher than that of P1 (Figure 20d). This trend is attributed to the stronger coupling ability of longer molecular chains with fluid shear forces and cavitation-induced stress fields.

[0117] To quantitatively analyze the activation efficiency, the maximum molar extinction coefficient (ε) of the ring-opening product was first measured in an acetic acid / acetonitrile mixed solution. max The calibration was performed, and ε was obtained. max = 2.84 × 10 4 L·mol - ¹·cm - ¹ (Fig. 20e). The activation rate after ultrasonic treatment was then calculated. The results showed that the activation rate gradually increased as the molecular weight increased from 67 kDa to 148 kDa, while the activation efficiency increased from 34% to 53% before reaching a plateau (Fig. 20f).

[0118] 8. Simulation calculation All calculations in this invention use model molecular structures that represent the structure after polymer integration (see Figures 21a-b). First, the mechanochemical reactivity was simulated using the CoGEF (constrained geometries simulate external force) method. The calculations employed the B3LYP / 6-31G(d) method, and were performed in both gas-phase and polar solvent models (acetonitrile, MeCN, see Figures 20c-d). The results show that selective breakage of the central CN bond occurs as expected when tensile forces are applied to M1 and M2. In the gas-phase model, the predicted maximum breaking force ( F max The values ​​are 4.92 nN and 4.86 nN, respectively; while under the acetonitrile solvent model, the predicted values ​​are... F max The values ​​are 4.76 nN and 4.70 nN, respectively, which are close to each other. It is worth noting that when a polarized continuum model is not introduced to simulate a polar solvent environment, the calculation predicts that an unexpected molecular rearrangement will occur after the CN bond breaks.

[0119] Furthermore, the force sensitivity and stability of the CN bonds in M1 and M2 were calculated using the restoring force triangle (RFT) model. The calculations employed the B3LYP / 6-31G(d) method to simulate the effective force constant of the easily fractured CN bonds under tensile stress. k eff (See Figure 22a). M1 and M2 k eff The structures exhibit similar energy barriers before and after heterolytic cracking of the CN bonds under zero force, and show similar results in the restoring force triangle model (see Figures 22b-c). This result indicates that their force sensitivity is approximately the same.

[0120] The energy changes before and after CN bond breaking and in the transition state were calculated using the DFT method (B3LYP / 6-31G(d)) under zero force (see Figure 22d). The results show that in the reverse reaction, the energy barrier of molecule M1 is lower than that of molecule M2, and lower than 21 kcal / mol at 298.15 K (see Figure 22e). This indicates that molecule M1 has a faster ring-closing rate than molecule M2 and can rapidly decolorize at room temperature. Furthermore, the change in free energy barrier under simulated external force was examined. It was found that the free energy barriers of both molecules decrease with increasing external force, which is consistent with the trend of force lowering the reaction energy barrier (see Figure 22f).

[0121] 9. Stability Analysis Thermogravimetric analysis showed that the temperature at which molecules lose 5% weight is 383 °C. NMR analysis indicated that the temperature at which this loss occurs in air is 275 °C. o Remains thermally stable below C (see) Figure 23 ).

[0122] Based on the results of P1 solutions before and after light and acid / alkali treatment, P1 did not exhibit significant color changes under these conditions. This demonstrates its non-color-developing properties to light and chemical stimuli, and its ability to develop color in a mechanoselective response. Figure 24 ).

[0123] The above description is merely a preferred embodiment of the present invention and is not intended to limit the invention. Various modifications and variations can be made to the present invention by those skilled in the art. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of the present invention should be included within the scope of protection of the present invention.

Claims

1. A mechanochromic molecule based on crystal violet lactam, characterized in that, The mechanochromic molecule is: 。 2. The mechanochromic molecule based on crystal violet lactone according to claim 1, characterized in that, The mechanochromic molecule is selected from any one of the following: Acrylamide and acrylate-terminated crystal violet lactam derivative M1: ; Diacrylate-terminated crystal violet lactam derivative M2: ; M3, a dibromo-terminated crystal violet lactam derivative: ; Dipentenoate-terminated crystal violet lactam derivative M4: 。 3. A polymer, characterized in that, The polymer is prepared by the following method: using methyl acrylate or polymethyl acrylate- co - Using ethylene glycol acrylate as a monomer and the mechanochromic molecule as a crosslinking agent according to claim 1 or 2, photopolymerization is performed to generate a single polymer network SN; in the monomer methyl acrylate or polymethyl acrylate- co - Swelling in a solution of ethylene glycol acrylate, crosslinking agent EGDMA, and TPO, followed by photopolymerization, yields a dual polymer network DN; swelling in a solution of methyl acrylate monomer or methyl acrylate / ethylene glycol acrylate, crosslinking agent EGDMA, and TPO, followed by photopolymerization, yields a triple polymer network TN.

4. A polymer, characterized in that, The polymer is prepared by the following method: using the mechanochromic molecule of claim 1 or 2 as an initiator, methyl methacrylate as a monomer, and Me6TREN as a ligand, a copper-catalyzed polymerization reaction is carried out under a nitrogen atmosphere to obtain a linear polymer.

5. A polymer, characterized in that, The polymer is prepared by blending the mechanochromic molecule described in claim 1 or 2 with the Sylgard® 184 prepolymer matrix, adding a curing agent, mixing thoroughly, pouring into a mold, and curing to obtain the polymer.

6. The application of the mechanochromic molecule as described in claim 1 or 2 in real-time stress monitoring, mechanical flaw detection visualization, information storage, or inkless writing.

Citation Information

Patent Citations

  • Phenolphthalein derivative-containing mechanochromic high polymer material with rapid self-recovery property and preparation method thereof

    CN109651587A

  • Thermochromic material with bicrystal violet lactone structure, color developing composition as well as preparation method and application of thermochromic material and color developing composition

    CN114163431A